Sonification of Golf Putting gesture reduces swing movement variability in Novices - O'Brien, B.; Juhas, B.; Bienkiewicz, M.; Buloup, F.; Bringoux, L.; Bourdin, C. (Research Quarterly for Exercise and Sport, 2021)
Purpose: To study whether novices can use sonification to enhance golf putting performance and swing movements. Method: Forty participants first performed a series of 2 m and 4 m putts, where swing velocities associated with successful trials were used to calculate their mean velocity profile (MVP). Participants were then divided into four groups with different auditory conditions: static pink noise unrelated to movement, auditory guidance based on personalized MVP, and two sonification strategies that mapped the real-time error between observed and MVP swings to modulate either the stereo display or roughness of the auditory guidance signal. Participants then performed a series of 2 m and 4 m putts with the auditory condition designated to their group. Results: In general our results showed significant correlations between swing movement variability and putting performance for all sonification groups. More specifically, in comparison to the group exposed to static pink noise, participants who were presented auditory guidance significantly reduced the deviation from their average swing movement. In addition, participants exposed to error-based sonification with stereo display modulation significantly lowered their variability in timing swing movements. These results provide further evidence of the benefits of sonification for novices performing complex motor skill tasks. Conclusions: More importantly, our findings suggest participants were able to better use online error-based sonification rather than auditory guidance to reduce variability in the execution and timing of their movements.